Evaluation of Structuring and Empowerment of Food Traders (PKL) in Sukabumi City - Windy Nurlita; Yana Fajar FY Basori; Tuah Nur (Program Pascasarjana Universitas Negeri Makassar, 2023)
The purpose of this study was to determine the evaluation of the government of Sukabumi City in the policy of structuring and empowering food traders (PKL) in Sukabumi City. This study uses qualitative research methods with a descriptive approach using data collection techniques, observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion/verification. The results of this study were measured by evaluation indicators by Agustino (2022) which showed that the Sukabumi City Government in evaluating policies for structuring and empowering food traders had not been maximized, this was due to the lack of good and strong cooperation between the local government and food traders. Food traders also only consider personal interests without looking at the rules they must comply with, this is the main factor in evaluations not running optimally.